Povidone-iodine ear wash and oral cotrimoxazole for chronic suppurative otitis media in Australian aboriginal children: study protocol for factorial design randomised controlled trial - Christine Wigger; Amanda Jane Leach; Jemima Beissbarth; Victor Oguoma; Ruth Lennox; Sandra Nelson; Hemi Patel; Mark Chatfield; Kathy Currie; Harvey Coates; Keith Edwards; Heidi Smith-Vaughan; et al. (BMC, 2019)
Abstract Background Chronic suppurative otitis media (CSOM) is a significant health issue affecting Aboriginal Australians. Long-term hearing loss can cause communication problems, educational disadvantage, and social isolation. Current standard treatment for CSOM in our region is twice daily dry mopping of the pus from the ear canal followed by instillation of ciprofloxacin antibiotic ear drops for up to 16 weeks, or until the discharge resolves for a period of 3 days. The treatment is long, laborious and fails to resolve ear discharge in 70% of cases in remote communities. Bacterial pathogens also persist. Povidone-iodine ear wash is the preferred method of clearing ear discharge in Western Australia. However, evidence of its effectiveness is lacking. In systematic reviews, topical antibiotics (ciprofloxacin) have been shown to be more effective than oral antibiotics or topical antiseptics. Currently, it is unclear whether there are any benefits of combining these treatments. Methods This protocol describes a 2 × 2 factorial randomised controlled trial of two different interventions (povidone-iodine ear wash and oral cotrimoxazole), given as adjunctive therapy to standard treatment for CSOM. 280 children, between 2 months and 17 years of age, Indigenous or non-Indigenous, living in participating Northern Territory (NT) communities are randomised to standard treatment (dry mopping and ciprofloxacin drops) plus one of two topical treatments (dilute povidone-iodine ear wash or no wash) and one of two oral medication treatments (16 weeks of cotrimoxazole or placebo). Discussion Current treatment of CSOM in our region shows that eradication of bacterial pathogens from the middle ear space and dry ears is often not achieved. This trial will evaluate the efficacy of adjunctive treatments of antiseptic ear washes and oral antibiotics. Clinical, microbiological and hearing outcomes will be reported. Trial registration This trial (ACTRN12614000234617) was registered with ANZCTR on 05 April 2014.